CONSERVATION AND RATIONAL USE OF OCEANS AND TERRITORIES FOR SUSTAINABLE DEVELOPMENT: CONCEPTS OF THE ARCTIC POLICY - Abdykakharov, Elaman; Vaslavskaya, Irina; Goloborodko, Ida; Leontev, Mikhail; Khaliapin, Aleksei; Grigoreva, Natalya (Veredas do Direito, 2026)
Technological advancements, economic prospects, and climate change have intensified discussions on governance solutions for aligning social and economic relations among governmental bodies at all levels, corporations, businesses, industries, and local populations, including indigenous Arctic communities. As a result, the Arctic governance system is evolving, influenced by repeated calls on the international stage to maintain the Arctic as a “zone of peace.” This governance is becoming more complex due to climate change and the responses of Arctic nations, each with strategic interests in the region. The article aims to identify the specific characteristics of sustainable development governance in the northern territories of Arctic nations in national and international contexts. The article considers cooperation among Arctic states in promoting the sustainable development of the Far North and the role of the Arctic Council in this process. Based on the case study “Concepts of the Arctic Policy among Arctic Nations for Sustainable Development”, the article concludes that the Arctic strategies of these nations should be grounded in multilateral cooperation on Arctic affairs. This approach would mitigate security issues in the region and reduce the risk of military conflicts by promoting transparency, predictability, stability, accountability, and pragmatic collaboration.